Sustained indentation in 2-D models of continental collision involving whole mantle subduction. Issue 1 (26th August 2022) - Laik, Arijit; Schellart, Wouter P; Strak, Vincent
SUMMARY: Continental collision zones form at convergent plate boundaries after the negatively buoyant oceanic lithosphere subducts entirely into the Earth's mantle. Consequently, orogenesis commences, and the colliding continents are sutured together. During the collision, plate convergence and motion of the sutured boundary towards the overriding plate are manifest in its deformation, as is the case for the long-term (∼50 Ma) and nearly constant convergence rate at the India–Eurasia collisional zone that hosts the Himalaya. However, despite the long history of modelling subduction-collision systems, it remains unclear what drives this convergence, especially in models where subduction is driven solely by buoyancy forces. This paper presents dynamic self-consistent buoyancy-driven 2-D whole-mantle scale numerical models of subduction-and-collision processes to explore variations in density and rheological stratification of the colliding continent and overriding plate (OP) viscosity (a proxy for OP strength) that facilitate post-collisional convergence and collisional boundary migration. In models with a moderately buoyant indenting continent, the collisional boundary advance is comparatively low (0.1–0.6 cm yr –1 ), and convergence is driven by the dense continental lithospheric mantle that continues to subduct as it decouples from its deforming crust. Conversely, models with a highly buoyant indenting continent show sustained indentation at 0.5–1.5 cm yr –1 until the slab detaches. Furthermore, models with a weaker OP and lower backarc viscosity show an enhanced propensity for indentation by a positively buoyant continent. These models additionally highlight the role of whole mantle flow induced by the sinking of the detached slab in the lower mantle as it sustains slow convergence at an average rate of 0.36 cm yr –1 for ∼25 Myr after break-off as well as prevents the residual slab from educting. In previous buoyancy-driven partial mantle depth models such eduction does generally occur, given that free-sinking of the detached slab in the mantle is not modelled. Although these findings widen the understanding of the long-term convergence of indenting continents, the lower post-collisional advance rates (0.3–1.5 cm yr –1 ) compared to India's approximate 1000–2000 km of northward indentation during the last 50 Myr attest to the need for 3-D models.